1992
DOI: 10.1002/iroh.19920770104
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Loss and Denitrification as Studied in Relation to Reductions in Nitrogen Loading in a Shallow, Hypertrophic Lake (Lake Søbygård, Denmark)

Abstract: A detailed mass balance on nitrogen was carried out in shallow and hypertrophic Lake SobygBrd during 4.5 years before through 2.5 years after a 36 % reduction in nitrogen loading. Annual mean loss rate of nitrogen was 159-229 mg N m-2 d-1 before the loading reduction and 125 mg N m-2 d-1 after. In spite of a short hydraulic retention time (18-27 days) the proportion of nitrogen loading lost in the lake was high (38-53 %) and not affected by changes in loading. Calculated denitrification accounted for 86-93 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 27 publications
4
32
1
Order By: Relevance
“…The extent of annual denitrification previously reported for Lake Søbygaard (35%-47% of total annual N loading [27]) was not fully achieved in this study (only 14%-35% of total annual N loading), which may explain why simulations did not fully reproduce minima of TN and inorganic N fractions during summer ( Figure 2C-E). Regular resuspension events caused by wind-induced shear stress and biological disturbances are known to have a major impact on the sediment-water nutrient exchange including nitrogen [48][49][50], subsequently enhancing denitrification [27,51]. Thus, low denitrification levels might be due to the relatively simple and empirical-based description of resuspension in PCLake [23].…”
Section: Model Calibration and Performancecontrasting
confidence: 68%
“…The extent of annual denitrification previously reported for Lake Søbygaard (35%-47% of total annual N loading [27]) was not fully achieved in this study (only 14%-35% of total annual N loading), which may explain why simulations did not fully reproduce minima of TN and inorganic N fractions during summer ( Figure 2C-E). Regular resuspension events caused by wind-induced shear stress and biological disturbances are known to have a major impact on the sediment-water nutrient exchange including nitrogen [48][49][50], subsequently enhancing denitrification [27,51]. Thus, low denitrification levels might be due to the relatively simple and empirical-based description of resuspension in PCLake [23].…”
Section: Model Calibration and Performancecontrasting
confidence: 68%
“…Also, we know from on site inspection that P enriched organic sediments rarely exist in the river and channel sections. According to Jensen et al (1992b) and Seitzinger (1988) nitrogen losses are mainly caused by two processes: denitrification and sedimentation. Both, nitrate reduction (Chapra, 1997) and settling of particulate N (Scheffer, 1998) can be described by first order kinetics.…”
Section: Quantification Of Nutrient Retentionmentioning
confidence: 99%
“…That is, the concentrations' rate of change depends linearily on the respective concentrations. Since Jensen et al (1992b) found denitrification in lakes to be closer related to the concentration of TN rather than to NO − 3 , a lumped first order term was tested for the description of total nitrogen retention (Eq. 2).…”
Section: Quantification Of Nutrient Retentionmentioning
confidence: 99%
“…Furthermore, a BMR nutrient budget for year 2008 [17], reported that over 60 % and 30% of nitrate and nitrite respectively that entered the reservoir were retained and permanently buried in the sediment, while the rest are estimated to be removed via denitrification. In Denmark, Jensen et al [18] found that nitrogen retention was indeed IConCEES 2015 05004-p.5 caused by denitrification. Akinbile et al [19] also did a study on addition to the analysis of phosphorus and nitrogen contents of the sediment in BMR and found out that the water was slightly polluted (Class III according to Malaysia Water Quality Index) at the highest concentration of nitrogen and phosphorus.…”
Section: -P4mentioning
confidence: 99%